Characteristics Associated with Early Worsening of Retinopathy in Patients with Type 2 Diabetes Diagnosed with Retinopathy at Their First Visit: A Retrospective Observational Study. (19th July 2021) - Sugawa, Sayaka Wakabayashi; Yoshida, Yoko; Hikima, Yusuke; Sato, Haruhiko; Shimada, Akira; Noda, Mitsuhiko; Kushiyama, Akifumi
Abstract : Aims/Introduction . To investigate whether the occurrence of early worsening of diabetic retinopathy in patients with type 2 diabetes diagnosed with simple or preproliferative diabetic retinopathy at their first visit differed according to HbA1c reduction and/or treatment intensification. Materials and Methods . Our study design was a retrospective observational study. Subjects with type 2 diabetes diagnosed with either simple or preproliferative diabetic retinopathy by ophthalmologists at their first visit and followed up for 6–18 months thereafter were included and divided into worsening and nonworsening groups. Thereafter, baseline characteristics and changes in HbA1c and therapy over a year were investigated. Results . Among the 88 subjects with simple diabetic retinopathy, 16% improved to no retinopathy, 65% retained their simple diabetic retinopathy, 18% worsened to preproliferative diabetic retinopathy, and 1% worsened to proliferative diabetic retinopathy. Among the 47 subjects with preproliferative diabetic retinopathy, 9% improved to simple diabetic retinopathy, 72% retained their preproliferative diabetic retinopathy, and 19% worsened to proliferative diabetic retinopathy. Patients with simple diabetic retinopathy had an odds ratio of 1.44 for worsening retinopathy with a 1% increase in baseline HbA1c. Meanwhile, the odds ratios for worsening retinopathy with a 1% decrease in HbA1c from baseline at 3, 6, and 12 months were 1.34, 1.31, and 1.38, respectively. Among patients with simple diabetic retinopathy, significantly more new interventions were introduced in the worsening group than in the nonworsening group. Conclusions . Increased baseline HbA1c, a substantial decrease in HbA1c, and intensified therapy were identified as risk factors for early worsening of diabetic retinopathy in patients with simple diabetic retinopathy at the first visit. Patients should therefore be intimately followed for retinopathy after their first visit.